Politički, socijalni i ekonomski okvir organizirane keramičke proizvodnje unutar vučedolskog društva - na primjeru lokaliteta iz istočne Slavonije - Miloglav, Ina (2013)
The paper presents an overview of the results of processing ceramic material from two Vučedol sites in eastern Croatia as well as other parameters by which the standardization and the organization of production placed within a socio-economic framework of particular community can be confirmed. A special emphasis is directed towards the level of standardization of ceramic vessels, which is visible not only in the shaping of ceramic vessels but also through raw material composition.
Projekt MZOS
HRV